PEMILIHAN PERANGKAT LUNAK REPOSITORI INSTITUSI PERPUSTAKAAN PERGURUAN TINGGI DI KOTA MALANG (STUDI KASUS DI PERPUSTAKAAN UNIVERSITAS BRAWIJAYA, PERPUSTAKAAN UNIVERSITAS NEGERI MALANG, DAN PERPUSTAKAAN UNIVERSITAS MUHAMMADIYAH MALANG) - Pramudyo, Gani; Hendrawan, Muhammad (BACA: Jurnal Dokumentasi dan Informasi, 2018)
The purposes of this research are to know, describe, and analyze institutional repository softwares selection in Universitas Brawijaya (UB) Library, State University of Malang (UM) Library, and University of Muhammadiyah Malang (UMM) Library, also comparing software features of institutional repository.This research is using multi-site case study method with qualitative approach. Data was collected by observation, interviews, use of documents and audio-visual material. The results of this research indicate that the selection of software in academic library needs to pay attention to four aspects of software selection: (1) as needed; (2) have a licence; (3) technical support, training, relevant documentation and maintenance; (4) staff responsible for the selection and evaluation of digital collection software and related services to meet user or community needs. The selection of institutional repository software is not appropriate, resulting in the UB Library to migrate data from BKG to Eprints and UMM Library to migrate manually from GDL to Eprints. Academic library needs to pay attention to right aspects of software selection in building and developing institutional repositories and features.